2019
DOI: 10.1021/acsnano.9b05383
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable π-Conjugated Oligomer Nanoparticles with High Photothermal Conversion Efficiency for Cancer Theranostics

Abstract: We developed a biodegradable photothermal therapeutic (PTT) agent, π-conjugated oligomer nanoparticles (F8-PEG NPs), for highly efficient cancer theranostics. By exploiting an oligomer with excellent near-infrared (NIR) absorption, the nanoparticles show a high photothermal conversion efficiency (PCE) up to 82%, surpassing those of reported inorganic and organic PTT agents. In addition, the oligomer nanoparticles show excellent photostability and good biodegradability. The F8-PEG NPs are also demonstrated to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
154
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(155 citation statements)
references
References 61 publications
0
154
0
1
Order By: Relevance
“…Interestingly, owing to the strong TICT effect, its absorption can be red‐shifted to the NIR‐region, further benefiting photothermal conversion under laser irradiation of 808 nm. The maximum PTCE of C6TI in the aggregation state thus can reach 90.0 %, which is much higher than most reported photothermal agents including ICG (Table S1) . Thanks to its excellent PTCE, C6TI serves as a NIR‐triggered PTT agent that can locally heat the tumor region to 53.4 °C and further induce complete cell necrosis (Figures S2–4).…”
Section: Methodsmentioning
confidence: 90%
“…Interestingly, owing to the strong TICT effect, its absorption can be red‐shifted to the NIR‐region, further benefiting photothermal conversion under laser irradiation of 808 nm. The maximum PTCE of C6TI in the aggregation state thus can reach 90.0 %, which is much higher than most reported photothermal agents including ICG (Table S1) . Thanks to its excellent PTCE, C6TI serves as a NIR‐triggered PTT agent that can locally heat the tumor region to 53.4 °C and further induce complete cell necrosis (Figures S2–4).…”
Section: Methodsmentioning
confidence: 90%
“…Herein, many immense efforts have been devoted to designing photo‐driven ROS‐ECBs that transform endogenous H 2 O 2 to O 2 for alleviating tumor hypoxia. These photo‐driven ROS‐ECBs could be partitioned into three categories, including catalase, MnO 2 , and the other alternative types (Fan et al, 2015; Li, Cheng, et al, 2017; Li, Wang, et al, 2017; Li et al, 2019). It has been demonstrated that catalase could efficiently catalyze H 2 O 2 to provide O 2 and subsequently relieve tumor hypoxia (Phua et al, 2019).…”
Section: Energy‐converting Biomaterials For Cancer Therapymentioning
confidence: 99%
“…Semiconducting polymers‐based photo‐converted H‐ECBs, such as polyaniline, polyaniline (PANI), polypyrrole (PPy), and conjugated donor–acceptor (D‐A) structures, are emerging as the distinctive hyperthermia agents due to their excellent optical and photothermal properties (Li, Liu, et al, 2019; Liu et al, 2020; Wang, Ma, Sheng, Wang, & Xu, 2018; Yang et al, 2020). For instance, Li, Xie, et al (2018) constructed a semiconducting polymer amphiphile (PCB1) with photothermic activity for enhanced cancer therapy (Figure 7c).…”
Section: Energy‐converting Biomaterials For Cancer Therapymentioning
confidence: 99%
“…[12][13][14][15] Diverse photothermal agents, including inorganic and organic materials, have been developed. [16][17][18][19][20][21] In general, photothermal agents can also simultaneously achieve photoacoustic imaging (PAI) owing to their efficient heating output that generates ultrasonic vibration within biological tissue. [22][23][24][25] The main advantage of PAI is the light in/sound out paradigm that would achieve an ultra-deep (5-7 cm) tissue imaging with high spatial resolution, which makes it a very useful tool for deep-tissue imaging.…”
Section: Introductionmentioning
confidence: 99%